Highly specific label-free molecular imaging with spectrally tailored excitation stimulated Raman scattering (STE-SRS) microscopy - Freudiger, Christian W. (2011)
Label-free microscopy with chemical contrast and high acquisition speed up to video-rate has recently been made possible by stimulated Raman scattering (SRS) microscopy. While SRS imaging offers superb sensitivity, the spectral specificity of the original narrowband implementation is limited, making distinguishing chemical species with overlapping Raman bands difficult. Here we present a highly specific imaging method that allows mapping of a particular chemical species in the presence of interfering species based on tailored multiplex excitation of its vibrational spectrum. This is done by spectral modulation of a broadband pump beam at a high-frequency (>1MHz), allowing detection of the stimulated Raman gain signal of the narrowband Stokes beam with high sensitivity. Using the scheme, we demonstrate quantification of cholesterol in the presence of lipids, and real-time three-dimensional spectral imaging of protein, stearic acid and oleic acid in live C.elegans.